The Relationship Organizations Climate and Workplace Bullying Among Nurses - Nurman Hidaya; Yulastri Arif; Dwi Novrianda (Universitas Pendidikan Indonesia, 2022)
Introduction : Bullying in the workplace is one of the psychological problems often experienced by nurses in the workplace that hurts individuals and organizations. Incidents of workplace bullying are common in highly stressful jobs. Objective: This study aims to find out the relationship between organizational climate and workplace bullying among nurses. Method: This study used a cross-sectional, descriptive study design. There were 235 nurses involved as participants taken with a proportional random sampling technique. To assess bullying among nurses in Bengkulu by using a Negative Action Questionaire-Revised (NAQR) instrument. Results: The results showed that of 235 nurses, there were (37.4%) of nurses who experienced workplace bullying. Three bullying actions most frequently reported were experienced by nurses every week/day is getting excessive workload, given work tasks that are not following their competence, and given the job by the target deadline is not possible. A total of (44.3%) of nurses said working in an environment with a less good organizational climate. There is a relationship between the organizational climate of bullying to nurses in the workplace with a value of p = 0.000. Discussion: An excellent organizational climate accompanied by a clear division of tasks can avoid conflicts and can prevent bullying in the workplace.